Pembangunan Multidimensi sebagai Upaya Pengentasan Kemiskinan (Forum Ilmu Sosial, 2018)
Poverty consists of several dimensions—physical, geographical, power, and economy. The most commonly discussed poverty is economic poverty. The goal of MDGs in poverty-related SDGs is changed into ‘no poverty’. This becomes a challenge in itself, so it is need to know the reality for its achievement. To create no poverty, there are many roles which are needed. Cooperation for multidimensional development and improvement is highly recommended. The poverty data of Bengkulu Province in 2007 to 2015 gives enough illustration that the number or percentage of poor people is fluctuating. Increasing the poor can also be caused by an increase in the poverty line. The solution offered is multidimensional development, started from human development. Human development is carried out by improving health, education, and worthy living standards. The worthy living standard is supported by economic development. Economic development is designed to be integrated between regions with each other so that each region is stimulated to develop local potentials respectively. To facilitate and support the economic movement, transportation network system will be created which pay attention to the form or shape of the region.